THE ROLE OF MULTIMEDIA TECHNOLOGIES IN THE TEACHING OF MATHEMATICS (Web of Teachers: Inderscience Research, 2025)
This article discusses the role of multimedia technologies in teaching mathematics. Multimedia tools, including interactive programs, video lessons, graphs and simulations, allow students to more easily and efficiently master mathematical concepts.